Lecturers’ Attitudes towards Online Teaching in the Learning Process - Mardiana, Harisa (Register Journal, 2020)
The author's interest is to investigate the lecturers' attitudes towards online teaching in the learning process which is the teaching for the 21st-century learning process and to seek the relationship among lecturers’ attitudes, online teaching and learning process. The problem is many lecturers in Tangerang City area are afraid of using technology and some of them are stuttered and technology illiterate. The lecturers still prefer face to face learning in the class more campuses have provided Moodle as a platform of learning. With the circumstances of Coronavirus, the learning has moved to e-learning. In this research, the author used a mixed-method and the number of respondents was 104, data collection was obtained from questionnaires sent via Google Form and distributed through WhatsApp to the lecturers in Tangerang City area. Data is translated into frequency and regression linear. The result showed that 73 lecturers change them toward e-learning and remain 27 lectures had difficulty in teaching online and preferred traditional learning. Keywords: Lecturers' attitudes, online teaching, and learning process